ANALISIS KEMAMPUAN MAHASISWA DALAM MERANCANG ASESMEN DIAGNOSTIK NON-AKADEMIK SISWA SEKOLAH DASAR - Albar, Joni (JURNAL PENDIDIKAN DASAR, 2025)
Abstract: The ability of prospective elementary school teachers to design non-academic diagnostic assessments is a crucial aspect of supporting a holistic learning process in primary education. This study aims to describe and analyze the competence of students from the Primary School Teacher Education (PGSD) Study Program at STKIP Melawi in understanding and applying the principles of non-academic assessment through the development of appropriate assessment instruments. Non-academic assessments encompass the identification of students' psychosocial aspects, emotional states, motivation, and learning environment—areas often overlooked in traditional classroom practices. Using a quantitative descriptive approach, this research examined five key aspects of student competence: conceptual understanding, formulation of assessment indicators, selection of assessment types and techniques, structural quality and completeness of the instrument, and the students’ ability to reflect and justify their assessment design. The results revealed that most students demonstrated a good level of conceptual understanding (60%), yet faced challenges in technical skills such as indicator formulation (43% categorized as adequate) and appropriate technique selection (47% categorized as adequate). Moreover, several students struggled to structure their assessment tools comprehensively and to provide contextual justifications based on real student conditions. These findings suggest that while students’ theoretical knowledge is developing, there remains a need for strengthening practical and reflective competencies. Keywords: Diagnostic Assessment, Non-Academic, Student Competence, PGSD, Abstrak: Kemampuan mahasiswa calon guru dalam merancang asesmen diagnostik non-akademik menjadi aspek penting dalam mendukung proses pembelajaran yang holistik di sekolah dasar. Penelitian ini bertujuan untuk menggambarkan dan menganalisis sejauh mana mahasiswa Program Studi Pendidikan Guru Sekolah Dasar (PGSD) STKIP Melawi mampu memahami dan mengimplementasikan prinsip-prinsip asesmen non-akademik dalam bentuk rancangan instrumen asesmen. Asesmen non-akademik sendiri mencakup identifikasi aspek psikososial, emosi, motivasi, hingga kondisi lingkungan belajar siswa, yang kerap kali diabaikan dalam praktik pembelajaran konvensional. Penelitian ini menggunakan pendekatan deskriptif kuantitatif dengan teknik analisis data melalui tabulasi frekuensi dan persentase terhadap lima aspek kemampuan, yaitu: pemahaman konsep, perumusan indikator, pemilihan bentuk dan teknik asesmen, kualitas struktur instrumen, serta refleksi dan justifikasi desain. Hasil menunjukkan bahwa sebagian besar mahasiswa memiliki pemahaman konsep yang baik (60%), namun mengalami tantangan dalam aspek teknis seperti merumuskan indikator (kategori cukup 43%) dan memilih teknik asesmen yang tepat (kategori cukup 47%). Selain itu, masih terdapat keterbatasan dalam menyusun struktur asesmen yang lengkap dan memberikan justifikasi yang berbasis pada kondisi nyata siswa. Kata Kunci: Asesmen Diagnostik Non-Akademik, Kemampuan Mahasiswa, PGSD, Instrumen Asesmen